Factors Influencing Drug and Substance Abuse among Secondary School Students in Zimbabwe - Chikuvadze Pinias; Saidi Enia (Richtmann Publishing, 2023)
The study was premised on factors that influence secondary school students’ participation in drug and substance abuse activities. In this context for data generation, analysis, and discussion, was guided by a framework comprised of the phenomenology and qualitative approach. For this study thirty students and six class teachers from one secondary school in Zimbabwe were purposively and conveniently sampled as sources of information for the issue under investigation respectively. Document analysis, focus group discussion, and personal interview were employed to generate data, which was later analyzed according to emerging themes. From the study, it was revealed that secondary school students were abusing a variety of drugs, and substances such as ganja cakes, among others. It was also noted that students at the secondary school under investigation were driven into drug and substance abuse activities due to peer pressure among others. With the aim to mitigate prevalence of drug and substance abuse amongst the students at selected secondary schools, it was advocated that peer counseling, establishing rehabilitation centers, the introduction of stiff disciplinary measures, and awareness campaigns. Therefore, it can be concluded that secondary school students’ participation in drug and substance abuse, within the school premises was largely influenced by multiple factors. It is in this context that the researchers recommend that in selected secondary school coaching of students secondary school students, teachers, and parents/guardians on the execution of peer counseling strategy to ease off secondary school students' participation in anti-social demeanors needs be reinforced. Received: 15 November 2022 / Accepted: 29 December 2022 / Published: 5 January 2023